Exploring How Professional Skepticism and Religiosity Influence Audit Quality Through Internal and External Traits - Ni Putu Danis Amara Santi; Dodik Ariyanto (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2026)
Users of financial statements are more likely to trust that the reports are free from misstatements and manipulation when audit quality is high. This research aims to examine the role of professional skepticism and religiosity in moderating the effects of independence and time budget pressure on audit quality at public accounting firms in Bali Province. Data were collected using questionnaires distributed to 74 auditors employed at these firms, selected through a saturated sampling approach. The data analysis was conducted using the PLS-SEM approach with SmartPLS software. The results of the bootstrapping analysis, or hypothesis testing, indicate that independence positively influences audit quality, while time budget pressure negatively affects it. The moderation effect test reveals that professional skepticism strengthens the negative impact of time budget pressure on audit quality but does not moderate the effect of independence. On the other hand, religiosity does not moderate the influence of either independence or time budget pressure.